Bacterial community response to environmental change varies with depth in the surface soil. (September 2022) - Barbour, Kristin M.; Weihe, Claudia; Allison, Steven D.; Martiny, Jennifer B.H.
Abstract: Bacterial communities in the organic leaf litter layer and bulk (mineral and organic) soil are sensitive to environmental change. However, despite close interactions between these communities, the leaf litter layer has historically been studied in isolation from the bulk soil. Whether bacterial response to environmental change is uniform throughout the surface soil remains unclear. Here, we simultaneously characterized how bacterial community composition in three surface soil layers (the leaf litter layer, 0–2 cm of bulk soil, and 0–10 cm of bulk soil) responded to a wildfire burning through a 13-year drought simulation in two adjacent ecosystems, a grassland and coastal sage scrubland. We found that bacterial communities in all three surface soil layers were distinct in composition and varied with drought, ecosystem type, and temporal variation. Moreover, the impact of these environmental changes on bacterial community composition decreased with depth in the surface soil. Bacterial response to drought was three-fold higher in the leaf litter layer than in the top 10 cm of bulk soil, with the drought treatment explaining 4.8% and 1.6% of the compositional variation, respectively. Wildfire altered bacterial composition in the leaf litter layer but not within the top 10 cm of bulk soil. Further, previous exposure of the bacterial communities in the leaf litter layer to drought did not influence its response to the wildfire. Thus, considering soil depth when assessing the impact of environmental conditions on the surface soil microbiome may improve predictions about the degree to which microbial communities, and therefore soil carbon, will respond to future environmental change. Highlights: Bacterial communities are distinct between leaf litter and surface bulk soil. Bacterial community response to environmental changes depended on soil depth. The impact of drought on surface soil bacterial communities decreased with depth. Wildfire altered bacterial community composition in leaf litter but not bulk soil.